Time in range is a tool for assessing the quality of glycemic control in diabetes - L. A. Suplotova; A. S. Sudnitsyna; N. V. Romanova; M. V. Shestakova (Сахарный диабет)
The presence of continuous glucose monitoring (CGM) systems has expanded diagnostic capabilities. The implementation of this technology into clinical practice allowed to determine the patterns and tendencies of excursions in glucose levels, to obtain reliable data concerning short-term glycemic control. Taking into consideration the large amount of obtained information using CGM systems, more than 30 different indicators characterizing glycemic variability were proposed. However, it is very difficult for a practitioner to interpret the data obtained due to the variety of indicators and the lack of their target values. The first step in the standardization of indices was the creation of the International Guidelines for CGM in 2017, where the Time in Range (TIR) (3,9–10,0 mmol/l, less often 3,9–7,8 mmol/l) was significant. To complement the agreed parameters and simplify the interpretation of obtained data using CGM, in 2019 the recommendations were prepared for the International Consensus on Time in Range, where TIR was validated as an additional component of the assessment of glycemic control along with HbA1c. In the literature review the issues of the association of TIR with the development of micro- and macrovascular complications in type 1 and 2 diabetes are considered. The relationship with other indicators of the glycemic control assessment was also analyzed and the dependence of insulin therapy on TIR was shown. TIR is a simple and convenient indicator, it has a proven link with micro- and macrovascular complications of diabetes and can be recommended as a new tool for assessing the glycemic control. The main disadvantage of TIR usage is the insufficient apply of CGM technology by the majority of patients with diabetes.